(untitled) (Actualizaciones en Sida e Infectología, 2022)
Background. The Cryptococcus´ colony-forming unit (CFU) count in cerebrospinal fluid (CSF) would be a reliable marker for patient prognosis and a simple and inexpensive tool. Objective. To evaluate the usefulness of the CFU count of Cryptococcus spp. And to compare it with the variations of Cryptococcus´ capsular antigen (CrAg) in CSF. Materials and methods. Clinical records of patients with aids-related meningoencephalitis caused by Cryptococcus assisted in our center between February 2016 and July 2020 were reviewed. CFU count and CrAg values ​​in CSF were evaluated during the evolution of the mycosis. Results and Discussion. Data from 94 clinical episodes of 85 patients with a total of 297 observations of CSF samples were analyzed. The importance of using the CFU count was evidenced as it is a viability and fungal load marker. Low CFU count did not necessarily coexist with low CrAg. Regarding the evolution over time, most of the patients were diagnosed with a high fungal load and its decrease occurred faster than that the one of AgCr. This would reflect the improvement of the patient, allowing behaviors to be taken in this regard.